CTA Project Completion Report: ICT integration in business cluster development in Ethiopia - Visser, Piet (Technical Centre for Agricultural and Rural Cooperation, 2020)
This CTA project works with an existing business cluster, around the Tsehay Union establishing an operational management system with maximising the use of ICT for: • The strengthening of the capacity of the union and their eventual business partners to manage the ICT supported operational management system. • Establishment of a demand-driven operational management system in 1 cluster/union consisting of: o farmer record-keeping (profiling) as traceability/quality assurance tool; o operational/inventory management tool for PC/unions, both inputs and outputs; and o sales projections and working capital needs. o The strengthening of the relationships and planning within the business cluster around Tsehay Union.